HISTOLOGICAL CHARACTERIZATION AND LYMPHOID DYNAMICS OF PEYER’S PATCHES IN THE FIRST 45 DAYS OF AGE OF ALPACAS - Roca L., Víctor (2014)
The study aimed to describe the histological features of Peyer’s patches in jejunum and ileum of 33 newborn alpacas from 0 to 45 days of age. Sections of jejunum and ileum were collected and fixed in 10% buffered formaldehyde. Standard histological slides stained with hematoxylin-eosin were obtained and poly-L-lysine coated slides were used for detection of T cells by immunohistochemistry using monoclonal antibodies against CD-8 marker aided by Histostain development system. Histologically, newborn alpacas showed organized and well defined intestinal mucosa-associated lymphoid tissue in both, jejunum and ileum. In animals older than 14 days of age, jejunal Peyer’s patches develop showing regions of active cells and other areas of undifferentiated lymphoid cells. It was also found a very active and positive reaction to CD8 marker on lymphocytes grouped in follicles and on Peyer’s patches of jejunum and ileum of animals from 6 to 10 days of age and onwards. The number of CD8 (+) lymphocytes increases according to the animal’s age. It is concluded that Peyer’s patches develop before birth in the ileum and jejunum, both locations being active after birth although ileal Peyer’s patches decrease in time while jejunal Peyer’s patches persist through lifespan.